ADJACENT-GROUP SPECTRAL TRANSFORMATION COMPLEX SIGNALS - D. L. Khodyko; S. B. Salomatin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
An algoritm presented by the adjacent-group transformation of the spectral properties of a cyclic shift of the signal is considered. The transformation is used to generate signals with a frequency-phase-shift keying and to search for complex signals.